Improving Ability in Reading the Qur’an for Students at Hidayatullah TPA Bogor Through the Art of Learning the Qur’an with the Tilawati Method - Rustamaji (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
This research will be carried out to know how to implement the tilawati method for students at TPA Hidayatullah Bogor in studying the Qur’an and various factors that influence this implementation process. This research was carried out using various data obtained from various research results and previous studies related to this research. The results of this study indicate that the implementation of the increased learning of the Qur’an through the tilawati method for the students at the Hidayatullah TPA went quite smoothly. This success is due to the good understanding possessed by the teachers in implementing this tilawati method, sufficient supporting facilities and infrastructure, adequate time allocation, and a fairly conducive environment for learning so that the students possess a spirit to be able to learn Al-Qur’an well through this tilawati method.